The Fight for Eternity in Paul Tillich's First World War Sermons - Birkler, Margrethe Kamille (The journal of ecclesiastical history, 2025)
This article analyses a selection of archival material written by Paul Tillich, particularly his early parish sermons and sermons from World War I. Although the themes of ‘eternity’ and ‘the soul’ are rare in the early parish sermons and only appear in the context of death or suffering, they play a predominant role in the World War I sermons. This article suggests that this is because, for Tillich, suffering became the interpretative key. Through his sermons amidst the suffering and devastation of war Tillich employed what he called the immanent way of theology.